Pengaruh Kebijakan Sekolah Dalam PPK Berbasis Budaya Sekolah Terhadap Revitalisasi Nilai Integritas - Mulyanti Mulyanti; Irawan Suntoro; Rohman Rohman (Jurnal Kultur Demokrasi, 2019)
The aim of this study was to examine the influences of school policy in strengthening character education based school culture towards revitalization of students’ integrity values at SMP Yadika Natar academic year 2018/2019. This study used quantitative method, and it involved 30 students as the respondents. The data were collected through questionnaire and analyzed by using linear regression and analysis of Variance with SPSS. The result of this study shows that (1) there is a significant influence between school policy (X1) and revitalization of students’ integrity values (Y), with coefficient determination 46.4%. (2) there is a significant influence between the strengthen of character education based school culture (X2) and revitalization of students’ integrity values (Y), with coefficient determination 66.1%. (3) there are significant influences among school policy (X1), the reinforcement of character education based school culture (X2) and revitalization of students’ integrity values (Y) with coefficient determination 66.5%. Therefore, the results of this study are expected to improve and to get used to implement school policy and character education based school culture in order to reach the values of revitalization to the students.Tujuan penelitian ini untuk menjelaskan pengaruh kebijakan sekolah dalam penguatan pendidikan karakter berbasis budaya sekolah terhadap revitalisasi nilai integritas siswa di SMP Yadika Natar Tahun Pelajaran 2018/2019. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian deskriptif kuantitatif. Sampel dalam penelitian ini sebanyak 30 orang. Hasil penelitian ini menunjukkan bahwa: (1) Terdapat pengaruh yang signifikan antara kebijakan sekolah (X1) terhadap revitalisasi nilai integritas siswa (Y) dengan koefisien determinasi sebesar 46,4%, (2) Terdapat pengaruh yang signifikan antara penguatan pendidikan karakter berbasis budaya sekolah (X2) terhadap revitalisasi nilai integritas siswa (Y) dengan koefisien determinasi sebesar 66,1%, (3) Terdapat pengaruh yang signifikan antara kebijakan sekolah (X1) dan penguatan pendidikan karakter berbasis budaya sekolah (X2) terhadap revitalisasi nilai integritas siswa (Y) dengan koefisien determinasi sebesar 66,5%. Kata kunci: kebijakan sekolah, penguatan pendidikan karakter berbasis budaya sekolah, revitalisasi nilai integritas siswa